Global Research Trend on Islamic Character in Quality Education: A Bibliometric Analysis from 2000 to 2025 - Aziz Muzaki; Muhammad Khoirul Huda; Suparman (KIPS Institute, 2025)
The phenomenon of Islamic Character holds a central position in the global effort to achieve Quality Education (SDG 4) amidst the challenges of globalization and digital disruption. Previous studies are often fragmented, leaving a gap in comprehensive quantitative understanding and global thematic mapping. This research aims to provide a thorough portrait of global research on Islamic Character within Quality Education from 2000 to 2025 by mapping publication dynamics, collaboration networks, and thematic clusters. The methodology employed is bibliometric analysis, utilizing the Dimensions database, the PRISMA framework, and VOSviewer software, which yielded a final sample of 11,092 articles. The results indicate a high level of research urgency (total 24,721 citations, peaking in 2023) and a strong resonance as an inter-SDG research nexus. The thematic visualization identifies two dense poles of debate: the Humanistic-Social Crisis Pole (focused on COVID and resilience) and the Technical-Systemic Solution Pole (focused on model and technology). Temporal analysis reveals a rapid shift in focus from Critical Reflection (2020–2022) toward Systemic Intervention (since 2023). Furthermore, a highly integrated collaboration network was discovered. This study concludes that the research field is rapidly moving from crisis response to the development of structured solutions, demanding a balance between humanistic ethics rooted in religious values and the effective utilization of technology to foster holistic human development.